Retinal microvascular abnormalities in major depression - Sadykov, Evgenii; Hosak, Ladislav; Stepanov, Alexandr; Zapletalova, Jana; Studnicka, Jan (Biomedical papers, 2024)
Background. The aim of our study was to find a possible association between retinal microvascular abnormality and major depression in a non-geriatric population. Method. The participants with major depression were hospitalised at the University Hospital in Hradec Kralove, Department of Psychiatry. Retinal images were obtained using a stationary Fundus camera FF450 by Zeiss and a hand-held camera by oDocs. Results. Fifty patients (men n=18, women n=32) aged 16 to 55 (men's average age 33.7 extpm9.9 years, women's average age 37.9 extpm11.5 years) were compared with fifty mentally healthy subjects (men n=28, women n=22) aged 18 to 61 (men's average age 35.3 extpm9.2 years, women's average age 36.6 extpm10.6 years) in a cross-sectional design. The patients were diagnosed with a single depressive episode (n=26) or a recurrent depressive disorder (n=24) according to the ICD-10 classification. Our results confirmed significant microvascular changes in the retina in patients with depressive disorder in comparison to the control group of mentally healthy subjects, with significantly larger arteriolar (P<0.0001) as well as venular (P<0.001-0.0001) calibres in major depression. Conclusion. According to the literature, acute and chronic neuroinflammation is associated with changes in microvascular form and function. The endothelium becomes a major participant in the inflammatory response damaging the surrounding tissue and its function. Because the retina and brain tissue share a common embryonic origin, we suspect similar microvascular pathology in the retina and in the brain in major depression. Our results may contribute to a better understanding of depression etiopathogenesis and to its personalized treatment.
Keywords: depression; retinal microvascular abnormality; biomarker; neuroinflammation